NEW OCCURRENCE OF ALKALINE ULTRAMAFIC ROCKS IN THE SOUTHERN SIBERIAN PLATFORM - Egorov A.P.; Men'shagin Yu.V.; Sekerin A.P.; Koshkarev D.A.; Denisenko E.P. (My University, 2003)
Alkaline ultramafic rocks associated with carbonatites in the southern margin of the Siberian Platform are restricted to the marginal suture (Main Sayan fault) [5, 6]. They are not promising for diamond potential. Despite the wide abundance of diamond and associated minerals in the alluvium, potentially diamondiferous alkaline ultramafic rocks were not found up to present in the central part of the platform within the Irkutsk amphitheater. In addition to the favorable geological situation, the presence of typomorphic minerals in mineral concentrates of this area also suggested the possibility of the occurrence of diamondiferous rocks. Our investigations made it possible to closely approach solution of this problem.